DEVELOPMENT OF ALTERNATIVE ENERGY IN UKRAINE: THE MODERN STATE AND EFFECTIVENESS OF MACHINERIES OF THE STATE ADJUSTING - Voloshin O.L. (Pressing Problems of Public Administration, 2015)
The modern state and problem aspects of development of alternative energy is analysed inUkraine. Effectiveness of machineries of the state adjusting and potential of development ofalternative energy is definite in Ukraine.